Six Sigma Project Critical Success Factor Prioritization Using MADM Technique (International Journal of Applied Research in Management and Economics, 2018)
Purpose–The purpose of this research paper is to study the enablers of Six Sigma and to establish a relationship among them using DEMATEL.Design/methodology/approach– The research paper presents a blend of the theoretical framework and practical applications. In the paper, 11 enablers of Six Sigma are identified from a literature survey. The required data were collected from five specialists, factory managers and maintenance managers who have worked in Six Sigma fields.Findings–Variable F8 (Committed workforce) is known as the influential and Variable F1 (ETML) is known as the effective. Other elements can be claimed to have a partial influence. Originality/value–knowing the key enablers and relationships among them can help organizations to develop Six Sigma competences. It is one of the foremost attempts to model enablers of Six Sigma. The paper provides useful insights into the Six Sigma implementers, consultants, and researchers.